GENETIC DIVERSITY OF Hemibagrus guttatus IN THAI NGUYEN PROVINCE BY RAPD MARKERS - Thi Hai Ha, Nguyen; Van Thang, Bui; Viet Vinh, Tran; Thao Van, Tran (Journal of Forestry Science and Technology, 2017)
Hemibagrus guttatus, which is a species of the Hemibagrus genus of Barridae, distributed in few large rivers in the mountains and only in the rapid and strong currents. Because the economic benefits from H. guttatus are very high, this is hunted in large numbers. This study evaluated genetic diversity of H. guttatus from 24 collected individuals in Thai Nguyen based on ten primers of RAPD marker. Results showed that the average genetic similarity value between the individuals studied was 69.6%, the genetic similarity was ranged from 0.57 to 0.89. The samples were divided into two groups based on the value of genetic similarity, in which the samples collected in Phu Luong district had a similarity value of 57% in one group, unlike the others with similarity value 65%. Following research creates a scientific basis and an important scientific proof to conservation and development of H. guttatus genetic resources in Thai Nguyen province.